Elucidating the Mechanisms Underlying Enhanced Drought Tolerance in Plants Mediated by Arbuscular Mycorrhizal Fungi - Cheng, Shen; Zou, Ying-Ning; Kuča, Kamil; Hashem, Abeer; Abd_Allah, Elsayed Fathi; Wu, Qiang-Sheng (Frontiers in Microbiology, 2021)
Plants are often subjected to various environmental stresses during their life cycle, among which drought stress is perhaps the most significant abiotic stress limiting plant growth and development. Arbuscular mycorrhizal (AM) fungi, a group of beneficial soil fungi, can enhance the adaptability and tolerance of their host plants to drought stress after infecting plant roots and establishing a symbiotic association with their host plant. Therefore, AM fungi represent an eco-friendly strategy in sustainable agricultural systems. There is still a need, however, to better understand the complex mechanisms underlying AM fungi-mediated enhancement of plant drought tolerance to ensure their effective use. AM fungi establish well-developed, extraradical hyphae on root surfaces, and function in water absorption and the uptake and transfer of nutrients into host cells. Thus, they participate in the physiology of host plants through the function of specific genes encoded in their genome. AM fungi also modulate morphological adaptations and various physiological processes in host plants, that help to mitigate drought-induced injury and enhance drought tolerance. Several AM-specific host genes have been identified and reported to be responsible for conferring enhanced drought tolerance. This review provides an overview of the effect of drought stress on the diversity and activity of AM fungi, the symbiotic relationship that exists between AM fungi and host plants under drought stress conditions, elucidates the morphological, physiological, and molecular mechanisms underlying AM fungi-mediated enhanced drought tolerance in plants, and provides an outlook for future research.